Gender Inequality and Foreign Direct Investment: Empirical Evidence from Asian Countries - Sujan Chandra Paul; Israt Jahan Rupa; Mallika Saha; Md. Abir Hossain (Faculty of Economic and Business, 2023)
In Asian countries, the relationship between gender inequality and foreign direct investment (FDI) is a sensitive topic. Due to labor market limits and the advantageous effect of women's empowerment, gender inequality is thought to have a detrimental impact on economic development and FDI. This study aims to look into the influence of gender disparity on FDI inflows to Asian countries. Our data includes 43 Asian nations and spans the years 1990 to 2018. We discover that reduced tertiary-level education and health gaps play a decisive role in FDI inflow into Asian countries using the Generalized Method of Moments (GMM). The findings are crucial to devising policies to minimize the gap in gender equality and promote FDI.JEL Classification: J01, J10How to Cite:Paul, S. C., Rupa, I. J., Saha, M., Hossain, M. A., & Sulltana, N. (2023). Gender Equality and Foreign Direct Investment: Empirical Evidence from Asian Countries. Etikonomi, 22(2), 321 – 332. https://doi.org/10.15408/etk.v22i2.27099.